Analysis of optimal environmental conditions for Microcystis blooms in large, shallow, eutrophic lakes. Issue 1 (1st January 2021) - Li, Meixia; Yu, Ruihong; Cao, Zhengxu; Jin, Ye; Sun, Heyang; Qi, Zhen
Abstract : Harmful algal blooms caused by cyanobacteria have detrimental impacts on lake ecosystems. Uncovering the factors influencing such blooms could facilitate aquatic ecosystem conservation and early warning activities. The experiment simulated the environmental characteristics of shallow eutrophic Lake Ulansuhai in arid regions of China. The experiments were conducted at various temperatures (6, 10, 19, 25°C) and different nutrient conditions (N: 1∼6 mg/L, P: 0.05∼1.00 mg/L) and in the presence of water, algae, and sediment under various disturbance levels (0, 100, 200, 250, 300, 350, 400 rpm). In this study, The optimal Microcystis growth conditions observed in the study were as follows: 19°C ≤ temperature ≤ 25°C; 1.0 mg/L ≤ N ≤ 1.6 mg/L; 0.05 mg/L ≤ P ≤ 0.1 mg/L; 16 ≤ N/P ≤ 20; and lake flow velocity = 10 cm·s −1 (200 rpm). The most suitable pH for the growth of Microcystis is 8.5. Investigating the environmental factors that affect the growth of bloom-forming cyanobacteria could aid the development of early warning systems and guide lake restoration activities under climate warming, N:P imbalance, and varying lake velocity scenarios.